Effect of the Peiyu granules on early miscarriage among women undergoing embryo transfer: a randomized, double-blind, placebo-controlled trial - He, Dandan; Lyu, Tianyi; Wang, Xiaonan; Ma, Yanmin; Lan, Yonglian; Yang, Xiaokui; Jia, Chanwei; Zhou, Liying; Liang, Yu; Li, Ying; Dai, Yinmei; Yue, Wentao; et al. (Frontiers in Endocrinology, 2025)
ObjectiveTo evaluate the efficacy and safety of the Peiyu Granules (PYG) compared with placebo on early miscarriage rates among women undergoing embryo transfer.MethodsA double-blind, parallel-group randomized clinical trial between February 15, 2017, and June 17, 2019, within 10 months of pregnancy follow-up until March 2020. This clinical trial was conducted at Beijing Obstetrics and Gynecology Hospital, Capital Medical University. A total of 886 women were included in this study. The intervention group (n = 443) received PYG on the night of Embryo Transfer (ET) until the day of the hCG test. If it was negative, the patient stopped taking medicine. In contrast, the treatment continued until 70 days after ET. The women in the control group (n = 443) consumed the same amount of placebo as the intervention group. All women enrolled were subject to the same follow-up protocols. The primary outcome was early miscarriage rate. The secondary outcomes were clinical intrauterine pregnancy rate and live birth rate.ResultsAmong the 886 randomized women (mean [SD] age, 32.8 [3.6] years), 854 women (96.4%) underwent ET and followed the treatment of random grouping. Early miscarriage occurred among 17 of 133 women (12.8%) receiving PYG compared with 35 of 156 women (22.4%) receiving placebo (relative risk[RR], 0.51 [95% CI, 0.27 to 0.95], P = 0.02). Clinical intrauterine pregnancy rates were 30.0% (133 of 443) in the intervention group and 35.2% (156 of 443) in the control group (relative risk[RR], 0.79 [95% CI, 0.60 to 1.05], P = 0.10). Live-birth rates were 25.3% (112 of 443) in the intervention group and 25.7% (114 of 443) in the control group (relative risk[RR], 0.98 [95% CI, 0.72 to 1.32], P = 0.88). Live birth rates in the clinical pregnant population were 84.2% (112/133) in the intervention group and 73.7% (115/156) in the control group (relative risk [RR], 1.14 [95% CI, 1.01 to 1.29], P = 0.03).ConclusionThe findings suggested that PYG reduced early miscarriage rates among women undergoing embryo transfer. However, there were no significant improvement in clinical pregnancy rates and live birth rates.Clinical trial registrationhttps://www.chictr.org.cn/showproj.html?proj=12343 identifier, ChiCTR-inr-16010087.